Vertically aligned carbon nanotube arrays as thermal interface material for vibrational structure of piezoelectric transformer. (29th May 2018) - Chen, Lie; Ju, Bin; Feng, Zhihua; Zhao, Yang
Abstract: The application and characterization of thermal interface material (TIM) for vibrational structures is investigated in this paper. The vibrating feature during the operation requires unique solution for its thermal management, since the connection between the device and heat dissipater should be able to conduct heat efficiently and impose minimum constraint onto the vibration simultaneously. As a typical vibrational device, piezoelectric transformers (PTs) are discussed in this paper. The PTs have urgent demands for thermal dissipation since their power conversion efficiency decrease rapidly with the rising temperature. A novel method by applying vertically aligned carbon nanotube (VACNT) arrays to the interface between PT and heat dissipater is presented to enhance the performance of piezoelectric transformers. VACNT arrays are one of the excellent TIMs. It can directly establish thermal contact between two surfaces by van der Waals' forces. In addition, the unique anisotropic character of CNT arrays provides enough flexibility to accommodate the vibration during the operation. Different configurations of TIMs are compared with each other in this work, including CNT arrays, tape of polypropylene (PP) membrane and without heat transfer structure (HTS). The results indicate that the temperature rise is lowest and the efficiency is highest at the same power density while CNT arrays served as the TIM. Almost no significant fretting and wearing damage occurred on PT electrode surface with CNT arrays TIM even after working continuously for 120 days. Meanwhile, the thermo-physical properties of CNT arrays at contact interface are measured by optical transient thermo-reflectance technique.